The impact of external facial features on the construction of facial composites. Issue 4 (3rd April 2019) - Brown, Charity; Portch, Emma; Skelton, Faye C.; Fodarella, Cristina; Kuivaniemi-Smith, Heidi; Herold, Kate; Hancock, Peter J. B.; Frowd, Charlie D.
Abstract: Witnesses may construct a composite face of a perpetrator using a computerised interface. Police practitioners guide witnesses through this unusual process, the goal being to produce an identifiable image. However, any changes a perpetrator makes to their external facial-features may interfere with this process. In Experiment 1, participants constructed a composite using a holistic interface one day after target encoding. Target faces were unaltered, or had altered external-features: (i) changed hair, (ii) external-features removed or (iii) naturally-concealed external-features (hair, ears, face-shape occluded by a hooded top). These manipulations produced composites with more error-prone internal-features: participants' familiar with a target's unaltered appearance less often provided a correct name. Experiment 2 applied external-feature alterations to composites of unaltered targets; although whole-face composites contained less error-prone internal-features, identification was impaired. Experiment 3 replicated negative effects of changing target hair on construction and tested a practical solution: selectively concealing hair and eyes improved identification. Practitioner Summary: The research indicates that when a target identity disguises or changes hair, this can lead to a witness (or victim) constructing a composite that is less readily identified. We assess a practical method to overcome this forensic issue. Abbreviation: GEE: Generalized Estimating Equations